Meningkatkan Keterampilan Problem Solving pada Materi Hukum Pascal Melalui Pembelajaran PBL di SMAIT As-Syifa Boarding School Subang - Fadhli Hadi Surya (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Pascal law material requires critical skills to study it, in order to get meaningful learning material. This research aims to improve problem solving skills in Pascal law material through PBL learning at SMAIT As-Syifa Boarding School Subang. The research method used is classroom action research with 2 cycles. Based on the results of action research carried out using the problem-based learning (PBL) model in class XI IPA 1 girls on Pascal law material, it shows the results of increasing students' problem-solving skills. So, the problem-based learning (PBL) model for learning problem solving skills can be an alternative media used by teachers. Improving the problem-solving skills of students in class held Class XI Science 1 Girls students from cycle I to cycle 2. showed satisfactory results and met the classical completeness criteria, namely from 95% to 97.5% of student activity and the problem skill score was above 75 after cycle 2 was completed. This study has limitations that need to be followed up by future researchers, such as revealing the effectiveness of problem-based learning in increasing students' learning motivation towards physics lessons through more comprehensive methods and objects.